2020
DOI: 10.21037/apm-20-1203
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study on different doses and fractionated radiotherapies for multiple brain metastases of non-EGFR mutant lung adenocarcinoma

Abstract: Background: To study the effects and adverse reactions of different doses and fractionated radiotherapies on non-epidermal growth factor receptor (EGFR) mutant lung adenocarcinoma patients with multiple brain metastases.Methods: In total, 80 patients eligible for inclusion were randomly divided into 4 groups. Group A included whole brain radiotherapy (WBRT) alone 300 cGy/fraction ×10 fractions, at a total dose of 3,000 cGy.Group B included WBRT alone 180 cGy/fraction ×22 fractions, at a total dose of 3,960 cGy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…More studies supported the opinion that WBRT is associated with inferior quality of life and precognitive function. The incidence rates of memory decline in the groups of WBRT were significantly more increased than in the non-WBRT group [ 30 ]. In RTOG 0933 [ 31 ], a single-arm phase II study of WBRT without hippocampal avoidance (WBRT-HA), mean relative decline in Hopkins Verbal Learning Test–Revised Delayed Recall (HVLT-R DR) was magnificently lower(7.0% VS. 30%, 95% CI:4.7% to 18.7%, P < 0.001) in comparison with the historical control, a published phase III trial (PCI-P-120–9801).…”
Section: Discussionmentioning
confidence: 99%
“…More studies supported the opinion that WBRT is associated with inferior quality of life and precognitive function. The incidence rates of memory decline in the groups of WBRT were significantly more increased than in the non-WBRT group [ 30 ]. In RTOG 0933 [ 31 ], a single-arm phase II study of WBRT without hippocampal avoidance (WBRT-HA), mean relative decline in Hopkins Verbal Learning Test–Revised Delayed Recall (HVLT-R DR) was magnificently lower(7.0% VS. 30%, 95% CI:4.7% to 18.7%, P < 0.001) in comparison with the historical control, a published phase III trial (PCI-P-120–9801).…”
Section: Discussionmentioning
confidence: 99%
“…While a number of individuals have experienced positive outcomes from radiotherapy, it can nevertheless result in various negative effects. For instance, research has demonstrated that whole-brain radiotherapy administered to patients with lung cancer and brain metastases will ultimately result in memory impairment ( 100 ). A retrospective cohort study found that patients with nasopharyngeal carcinoma had a higher incidence of oral mucositis during radiotherapy ( 101 ).…”
Section: Impact Of Microbial Metabolites On Clinical Cancer Therapymentioning
confidence: 99%
“…Because the patient had symptoms of high intracranial pressure and deterioration of dizziness, the patient and his family members refused biopsy. ALKr wasn s report [5], the patient was given the whole brain radiation therapy (WBRT) combined with simultaneous integrated boost (SIB) which aimed at metastatic focuses. WBRT was delivered in a course of 39.6 Gy in 22 fractions.…”
Section: Case Presentationmentioning
confidence: 99%